Analisis Kebijakan Fiskal: Dampak Terhadap Pertumbuhan Ekonomi di Kota Tanjungpinang - A, Abraham; Pangestoeti, Wahjoe; Sari, Tiara Ayu Puspita; Khoirunnisa, Afrija (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Tanjungpinang City, as the capital of Riau Islands Province, has great potential to develop into an economic and tourism center in the region. However, to achieve this potential, appropriate policies are needed, including effective fiscal policies. This study This aims to analyze the influence of financial policy on the economic growth of Tanjung Pinang City. The information used in this research is secondary information obtained from various sources such as government reports, the Central Statistics Agency and literature. Data analysis shows that the financial policies implemented by the Tanjung Pinang city government have had a positive impact on the city's economic growth. This is indicated by an increase in gross domestic product (GRDP), a decrease in unemployment and an increase in investment. However, there are several challenges ahead, including the high dependence of Tanjung Pinang City on the tourism sector. Therefore, it is necessary to diversify the economy and improve the quality of infrastructure and human resources. increase the city's competitiveness.